Vol 1 Maret 2023 MEMPERKUAT LITERASI KEUANGAN DAN INVESTASI SYARI'AH: UNSUR NAJSYI DALAM AFILIASI BINARY OPTION - Misbahun nidhom (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2023)
The capital market plays an important role for the progress of the Indonesian economy. In addition, the capital market can also be an alternative investment for investors. The capital market in a narrow sense is a stock exchange or a place to trade securities for investors. This means that the capital market is a place where parties who need capital or funds meet with those who have excess funds. While the capital market in a broad sense is a means used by people who need long-term capital. Parties who need capital are the private sector or the government and the public, also known as investors.